1969
DOI: 10.1172/jci106136
|View full text |Cite
|
Sign up to set email alerts
|

Study of calcium absorption in man: a kinetic analysis and physiologic model

Abstract: A B S T R A C T A physical model of calcium absorption was developed from analysis of data obtained on 23 subjects, including 13 patients having a variety of abnormalities of calcium metabolism. The model was tested and found consistent in all subjects studied. This technique provides a quantitative description of the rate of entry of oral dose of 'TCa into the circulation as a function of time by analysis of serum or forearm radioactivity in response to intravenous and oral administration of 'TCa. The kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
11

Year Published

1972
1972
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(60 citation statements)
references
References 17 publications
3
46
0
11
Order By: Relevance
“…Both possibilities were considered in previous studies (3)(4)(5). The hypercalcemic action of PTH is a result of its skeletal mobilization of calcium and increased gastrointestinal absorption of calcium (16)(17)(18)(19). The results of our study confirmed the previously reported hypocalciuric effect of PTH in hypoparathyroid patients (17) and demonstrated it also in normal subjects.…”
Section: Resultssupporting
confidence: 88%
“…Both possibilities were considered in previous studies (3)(4)(5). The hypercalcemic action of PTH is a result of its skeletal mobilization of calcium and increased gastrointestinal absorption of calcium (16)(17)(18)(19). The results of our study confirmed the previously reported hypocalciuric effect of PTH in hypoparathyroid patients (17) and demonstrated it also in normal subjects.…”
Section: Resultssupporting
confidence: 88%
“…20,21 It is unlikely that we missed transient increases in serum mineral levels before the first postprandial time point when we sampled blood and urine, because the maximal gastrointestinal absorption of calcium and phosphorus occurs 40 to 60 min after a meal. 22 Furthermore, if efficient gastrointestinal absorption occurred earlier, then we should have observed a different response between the meals. An alternative hypothesis is that neurohormonal changes associated with eating led to renal vasodilation with an increase in glomerular filtration of calcium and phosphorus and a decrease in their tubular reabsorption that was independent of serum levels and intake.…”
Section: Clinical Research Wwwjasnorgmentioning
confidence: 92%
“…O local onde a maior parte da absorção do elemento vai ocorrer depende da capacidade absortiva, do comprimento do segmento intestinal, do tempo de trânsito, da biodisponibilidade e da concentração intraluminal de Ca (3). O duodeno tem a maior capacidade absortiva por unidade de comprimento, mas a maioria do Ca é absorvida no jejuno devido ao seu maior comprimento total (4,5).…”
Section: Fatores Fisiológicos E Biodisponibilidade Do Cálciounclassified
“…Contudo, com exceção das gorduras e algumas drogas, estes compostos têm pouca importância prática na vida diária (3,4). O Ca e o fósforo (P) absorvidos participam da manutenção da absorção do Ca devido aos efeitos do Ca sérico sobre a secreção do PTH e dos efeitos do P e PTH séricos sobre a produção renal de 1,25(OH) 2 D (9).…”
Section: Fatores Fisiológicos E Biodisponibilidade Do Cálciounclassified